Pharmacokinetic Properties ofAnti‐Influenza Neuraminidase Inhibitors. (24th January 2013) - Chairat, Kalayanee; Tarning, Joel; White, Nicholas J.; Lindegardh, Niklas
Abstract Neuraminidase inhibitors are the mainstay of anti‐influenza treatment. Oseltamivir is the most widely used drug but is currently available only as an oral formulation. Resistance spreads rapidly in seasonal H1N1 influenza A viruses, which were universally resistant in 2008, because of the H275Y mutation in the neuraminidase (NA) gene. Oseltamivir is a prodrug for the active carboxylate metabolite. Ex vivo conversion in blood samples may have confounded early pharmacokinetic studies. Oseltamivir shows dose linear kinetics, and oseltamivir carboxylate has an elimination half‐life (t1/2β) after oral administration in healthy individuals of approximately 7.7 hours. Oseltamivir carboxylate is eliminated primarily by tubular secretion, and both clearance and tissue distribution are reduced by probenecid. The H275Y mutation in NA confers high‐level oseltamivir resistance and intermediate peramivir resistance but does not alter zanamivir susceptibility. Zanamivir is available as a powder for inhalation, and a parenteral form is under development. Zanamivir distributes in an apparent volume of distribution approximating that of extracellular water and is rapidly eliminated (t1/2β of approximately 3.0 hours). Peramivir is slowly eliminated (t1/2β of 7.7‐20.8 hours) and is prescribed as either a once‐daily injection or as a single infusion. Laninamivir is a recently developed slowly eliminated compound for administration by inhalation.